Acidification tolerance of Barbonymus schwanenfeldii (Bleeker, 1854) and oreochromis niloticus (Linnaeus, 1758) – Implication of fish size - Lee, Nyanti; Nik Nurul Kamila, Abu-Rashid; Ling, Teck Yee; Soo, Chen Lin; Sim, Siong Fong; Jongkar, Grinang (BIOFLUX SRL, 2017)
The aim of the present study was to investigate the acidification tolerance of a Malaysian indigenous fish species, Barbonymus schwanenfeldii (Bleeker, 1854) and an exotic fish species, Oreochromis niloticus (Linnaeus, 1758). The survival rate, growth performance, and feed conversion ratio of fry and juvenile fish of B. schwanenfeldii and O. niloticus were tested in acidic water at pH 4.5, 5.5, and 6.5 for a period of 30 days. The fish reared in pH 7.0 acted as a control. The present study demonstrated that acidification in water reduced the survival rates of B. schwanenfeldii and O. niloticus and had a detrimental effect particularly on the survival of B. schwanenfeldii fry where a 100% mortality occurred under the exposure to pH 4.5. Additionally, the total length gain decreased significantly in the fry of both species when they were exposed to low pH water. The results also showed that acidification of water had more effect on fry than juvenile fish and acidification tolerance of the indigenous species B. schwanenfeldii was lower than the exotic species O. niloticus. The present study demonstrated the necessity to protect the indigenous species in Malaysia by maintaining a suitable water pH value in the natural habitat. © 2017, BIOFLUX SRL. All rights reserved.